Internalizing Islamic Education Values based on National Heroes in the Millennial Generation in the Minangkabau Tribe - Febriani, Suci; Hanif, Muhammad; Fadhil, Muhamad; Bedra, Kddour Guettaoi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
Character education is the main domain in balancing the cognitive abilities of learners. As the process of internalizing the values ​​of Islamic education can be adopted through the example of the heroes. This is due to the lack of critical studies related to the development of exemplary-based Islamic educational values​​, especially for the millennial generation. On that basis, this study aims to investigate the internalization of Islamic education values ​​based on the example of national heroes in the millennial generation. This study adopted a qualitative approach with a phenomenological study method in the millennial generation in the Minangkabau. The sample used was 33 students from various universities with Minangkabau ethnic backgrounds. Analysis of the data used is based on triangulation techniques with three ways of collecting data including limited interviews, observation and documentation. The results show that the values ​​of Islamic education in the millennial generation can be internalized through the adoption of exemplary figures. The research findings identify that the examples of the heroes are able to encourage the internalization of the values ​​of Islamic education in the millennial generation in the Minangkabau tribe. This study recommends further research to use a variety of ethnic samples and study topics